Promoting Clean Tourism and Waste Management Education at Paradiso Beach Kupang - Batilmurik, Ridolof; Fanggidae, Jappy P; Noach, Robert M; Ringa, Maria; Benu, Yessi S; Nurdin, Hairil; Dewiaty, Irmina L; Fanggidae, Enjelina (Jurnal Pengabdian dan Pemberdayaan Banyuwangi (Jurnal Abdiwangi), 2025)
Paradiso Beach, located in Oesapa Barat Subdistrict, Kupang, holds significant potential as a leading tourist destination. However, inadequate environmental management—particularly concerning waste management—remains a major challenge. This Community Service Program (PKM), conducted by the Department of Business Administration at the State Polytechnic of Kupang, aims to raise public awareness of the importance of waste management, improve the quality of tourism services, and empower micro-enterprises through the utilization of recycled waste. This initiative contributes to enhancing environmental quality and the economic well-being of communities surrounding Paradiso Beach. The results of this community service activity show that educational and outreach programs involving more than 100 participants successfully enhanced public understanding of environmentally friendly waste management. Approximately 75% of participants demonstrated behavioral changes in waste disposal and segregation. The program also facilitated the establishment of three environmental awareness groups and provided training on recycling-based waste management, which led to the creation of economically valuable products. As a result, the cleanliness of Paradiso Beach improved significantly, with a 40% reduction in waste and an 85% increase in visitor satisfaction. Moreover, three micro-enterprises based on recycled materials were established and began marketing their products to the local market. These activities demonstrate that a participatory approach can effectively raise environmental awareness and promote local economic development through sustainable waste management